Distribution and antimicrobial resistance patterns of urinary pathogens in preoperative midstream urine cultures from Chinese patients with urinary calculi: a meta-analysis - Xin Mei; Shike Zhang; Peng Xu; Zhican He; Ruizheng Tang; Baotong Yang; Iqbal Muhammad Sarfaraz; Wenqi Wu (BMC Urology, 2024)
Abstract Background and objective This study comprehensively evaluates the distribution patterns and antimicrobial resistance profiles of urinary pathogens in Preoperative midstream urine cultures collected from patients with urinary calculi in China over the last two decades. Methods A cross-sectional analysis of 41 studies was conducted. A systematic search across various databases, including Wanfang Data, CNKI, SinoMed, Embase, PubMed, and Web of Science, was carried out, covering the time period from 2002 to 2022. Using R 4.2.1 software, a meta-analysis was performed to assess heterogeneity using Cochran’s Q test and the I2 statistic. Results In the analysis of preoperative midstream urine cultures from Chinese patients with urinary calculi, gram-negative bacteria dominated at 69%, with Escherichia coli (43%), Klebsiella pneumoniae (8%), Proteus mirabilis (6%), Pseudomonas aeruginosa (5%), Acinetobacter baumannii (3%), and Enterobacter cloacae (4%) being prominent. Gram-positive organisms included Enterococcus faecalis (9%), Enterococcus faecium (5%), and Staphylococcus aureus (4%). Over time, proportions of Proteus mirabilis, Enterococcus faecalis, and Staphylococcus aureus decreased, while Klebsiella pneumoniae and Pseudomonas aeruginosa increased. Notably, Escherichia coli proportion reduced from 37 to 33% within the last two decades. Antimicrobial resistance analysis indicated declining resistance in E. coli (e.g., co-trimoxazole from 73 to 55%, gentamicin from 64 to 40%), but rising resistance in piperacillin and cefotaxime (34–60%). Enterococcus faecalis exhibited increasing resistance to ampicillin (5–69%), gentamicin (59–94%), and tetracycline (77–89%) over time, while resistance to levofloxacin and ciprofloxacin notably decreased (72–16% and 49–8%, respectively). Conclusion Over the past two decades, the proportion of gram-negative bacteria was declined, while the proportion of gram-positive bacteria increased. Escherichia coli remained the most common pathogen in the urine culture of patients with urinary calculi in China and the resistance of Escherichia coli to commonly used antibiotics increased. Clinicians should select appropriate antibiotics according to the results of urine culture and drug sensitivity test to reduce the occurrence of antibiotic resistance.